Unbiased high-throughput screening of drug-repurposing libraries identifies small-molecule inhibitors of clot retraction - Lorena Buitrago; Miriam-Rose Menezes; Chloe Larson; Jihong Li; Thomas Kartika; Priyam Banerjee; Fraser Glickman; Barry Coller (Blood Advances)
Abstract: Platelet clot retraction, the ultimate phase of platelet thrombus formation, is critical for clot stabilization. It requires functional αIIbβ3 receptors, fibrin, and the integrated actions of the actin-myosin contractile and cytoskeletal systems. Disturbances in clot retraction have been associated with both bleeding and thrombosis. We recently demonstrated that platelets treated with the αIIbβ3 antagonist peptide Arg-Gly-Asp-Trp, which eliminates fibrinogen-mediated platelet aggregation, are still able to retract clots. We have exploited this observation to develop an unbiased, functional high-throughput assay to identify small-molecule inhibitors of fibrin-mediated clot retraction adapted for a 384-well plate format. We tested 9710 compounds from drug-repurposing libraries (DRLs). These libraries contain compounds that are either US Food and Drug Administration approved or have undergone preclinical/clinical development. We identified 27 compounds from the Library of Pharmacologically Active Compounds library as inhibitors of clot retraction, of which 14 are known inhibitors of platelet function. From the DRLs, we identified 135 compounds (1.6% hit rate). After extensive curation, these compounds were categorized based on the activity of their reported target. Multiple kinase and phosphodiesterase inhibitors with known antiplatelet effects were identified, along with multiple deubiquitination and receptor inhibitors, as well as compounds that have not previously been reported to have antiplatelet activity. Studies of 1 of the deubiquitination inhibitors (degrasyn) suggest that its effects are downstream of thrombin-induced platelet-fibrinogen interactions and thus may permit the separation of platelet thrombin-induced aggregation-mediated events from clot retraction. Additional studies of the identified compounds may lead to novel mechanisms of inhibiting thrombosis.